Peran Pegawai Bagian Urusan Tata Usaha Dalam Penanganan Surat Masuk Dan Surat Keluar Sistem Manual - Anitasari, Yeni; Fitriyani, Sani (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In any hospital, administrative staff definitely play a role in handling letters. The role of the letter processing employee is the daily work of processing incoming and outgoing letters, which can be managed properly and correctly. Knowing the role of an employee is a prerequisite for success in a hospital. The research method uses descriptive qualitative methods. The data collection technique was through direct observation and interviews on June 13, 2024. The data source used purposive sampling technique. The results of the survey show that administrative employees use manual system correspondence services as an official communication tool. The administration plays an important role in the operation of the hospital to ensure that all incoming and outgoing letters can be well managed. There is still a manual system for mail processing. The phases of mail processing begin with the receipt of the letter through to the archiving of the letter. The hurdles for employees are that typographical errors often occur in incoming letters as employees are often in a hurry when writing letters and parts of incoming letters are sometimes incomplete, such as: E.g. missing letter numbers, dates, subject lines, etc. To solve this problem, the employee must transcribe the incoming letter clearly and correctly into the diary book. If the part of the letter is incomplete, the employee can enter it according to the existing part of the appointment calendar letter.